DEFECT REDUCTION STRATEGY: SELECTING THE RIGHT MANAGEMENT TOOLS - Lisdiana; Setiyo Purwanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to improve product quality by applying the Total Quality Management (TQM), Supply Chain Management (SCM) and Six Sigma (SS) analysis approach as an effective improvement strategy to reduce the number of defects in the production process. This research method uses a quantitative method involving field surveys, data collection, and statistical analysis to identify the factors that cause dominant defects in the hydrogel production cycle in Wook Global Tecknology, PT using SmartPLS through an outer model tester, inner model and hypothesis testing. The sample used is a saturated sample, namely all employees in the quality control, totaling 83 employees. By identifying deviations from predetermined quality standards, this research aims to increase accuracy and consistency in the process production. The research results show that TQM and SCM does not have a significant effect on reducing product defect (RPD), but SS has a significant effect on reducing defective product.